2012
DOI: 10.1094/pdis-08-11-0653
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pseudomonas cichorii Associated with Leaf Spot on Soybean in South Korea

Abstract: Unusual symptoms were observed on 5% of the soybean (Glycine max (L.) Merill) plants in commercial fields in South Korea in September 2008 and 2009. The lesions were at first water soaked, then enlarged and turned dark brown or black, often with concentric white rings and sometimes surrounded by a bright yellow halo. Most lesions were roughly circular to irregular. Six bacteria were isolated on tryptic soy agar (TSA) media from plants of soybean cv. Daewon. The isolate JBC1 formed colonies that were whitish to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Bacterial strains. P. cichorii strain JBC1, which causes leaf spot on soybean, midrib rot on lettuce, and leaf spot and stem necrosis on tomato (46) was used in this experiment. The bacterial pathogen strains were picked from glycerol stock (-80°C) and inoculated in Luria-Bertani (LB) agar plates supplemented with vancomycin for P. cichorii JBC1 and cultured at 25°C as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial strains. P. cichorii strain JBC1, which causes leaf spot on soybean, midrib rot on lettuce, and leaf spot and stem necrosis on tomato (46) was used in this experiment. The bacterial pathogen strains were picked from glycerol stock (-80°C) and inoculated in Luria-Bertani (LB) agar plates supplemented with vancomycin for P. cichorii JBC1 and cultured at 25°C as needed.…”
Section: Methodsmentioning
confidence: 99%
“…() isolated P. cichorii from stem and pith necrosis of tomato and leaf spot of the dwarf umbrella tree in Turkey. Moreover, Yu & Lee () reported that P. cichorii is the causal agent of leaf spot on soybeans in South Korea. In view of the multihost range and severe economic losses worldwide, the development of appropriate disease control measures against this destructive pathogen is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas cichorii JBC1 was reported to be the causal agent of leaf spot on soybeans in South Korea (Yu & Lee, ), and is highly virulent. This strain also infects a wide range of other host plants, which includes economically important vegetables such as tomato and cabbage.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas cichorii identification in diseased samples have been accomplished mostly using morphological, physiological and biochemical methods (S anchez et al, 2003;Cottyn et al, 2009;Yu & Lee, 2012;Imriz & C ß inar, 2015). Recently, an ELISA-based method for strains that cause pith necrosis on tomato plants with potential use in the detection of coffee-associated strains was reported (Imriz & C ß inar, 2015).…”
Section: Pathogen Detectionmentioning
confidence: 99%